2000
DOI: 10.1046/j.1469-8137.2000.00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative kinetic analysis of ammonium and nitrate acquisition by tropical lowland rice: implications for rice cultivation and yield potential

Abstract: Nitrogen limitation compromises the realization of yield potential in cereals more than any other single factor. In rice, the world's most important crop species, the assumption has long been that only ammonium-N is efficiently utilized. Consequently, nitrate utilization has been largely ignored, although fragmentary data have suggested that growth could be substantial on nitrate. Using the short-lived radiotracer "$N, we here provide direct comparisons of root transmembrane fluxes and cytoplasmic pool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
102
0
15

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(121 citation statements)
references
References 53 publications
3
102
0
15
Order By: Relevance
“…In non-aerated paddy fields, rice mobilizes ammonium (NH 4 + ) rather than nitrate (NO 3 − ) as the preferred N source (Fried et al 1965;Sasakawa and Yamamoto 1978). Yet, plant growth, yield and N-use efficiency are significantly enhanced when NH 4 + and NO 3 − are provided simultaneously (Kronzucker et al 1999;Kronzucker et al 2000;Duan et al 2007). In well-drained, aerobic soils, the NH 4 + /NO 3 − ratio shifts rapidly towards the highly mobile N-source NO 3 − (Kirk and Kronzucker 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-aerated paddy fields, rice mobilizes ammonium (NH 4 + ) rather than nitrate (NO 3 − ) as the preferred N source (Fried et al 1965;Sasakawa and Yamamoto 1978). Yet, plant growth, yield and N-use efficiency are significantly enhanced when NH 4 + and NO 3 − are provided simultaneously (Kronzucker et al 1999;Kronzucker et al 2000;Duan et al 2007). In well-drained, aerobic soils, the NH 4 + /NO 3 − ratio shifts rapidly towards the highly mobile N-source NO 3 − (Kirk and Kronzucker 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In well-drained, aerobic soils, the NH 4 + /NO 3 − ratio shifts rapidly towards the highly mobile N-source NO 3 − (Kirk and Kronzucker 2005). Indeed, experiments with partial NH 4 + and NO 3 − supply and model calculations revealed that NO 3 − absorption and assimilation by wetland plants like rice is particularly efficient (Kronzucker et al 1999;Kronzucker et al 2000;Kirk and Kronzucker 2005;Duan et al 2007). Nevertheless, the agronomic practice of alternating flooding and draining of paddy rice fields may cause loss of up to 50% of applied N via nitrification-denitrification processes (Aulakh and BijaySingh 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Cereals like rice are poor in their nitrogen use efficiency (25-30 %) and grain protein content (~6 %). Radiotracer studies suggested that indica rice utilizes nitrate better than ammonia, the predominant form of N in flooded fields fertilized with urea (Kronzucker et al, 2000). The enzymes and genes of Nmetabolism in rice are known (Choi et al, 1989;Sakamoto et al, 1989;Goto et al, 1998) and their regulation by N metabolites and signaling processes have also begun to be understood (Ali et al, 2007a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, o aumento da percentagem de NH 4 + é prejudicial, diminuindo o teor de nitrato no pecíolo de plantas de algodão e a atividade da enzima redutase do nitrato, e aumentando o conteúdo de nitrogênio amoniacal em todos os órgãos do algodão (Dong et al, 2004). Kronzucker et al (2000) e Britto et al (2001) propuseram outro mecanismo, que estaria associado à toxidez por NH 4 + . Para esses autores, o fato de a absorção excessiva de NH 4 + ocorrer por transportadores de baixa afinidade e de ocupar canais de outros cátions indica que esse possa ser o motivo de se criar um mecanismo de efluxo do NH 4 + para fora da célula.…”
Section: Figuraunclassified
“…Esse mecanismo foi chamado, por esses autores, de Ciclagem Fútil, e o efeito resultante é um elevado gasto energético, necessário para bombear o excesso de NH 4 + para fora da célula. Conforme Kronzucker et al (2000) e Britto et al (2001), cerca de 80% do amônio absorvido pode sofrer efluxo por Ciclagem Fútil e o elevado consumo de energia na forma de ATP resulta no aumento da respiração nas raízes, causando redução no seu crescimento. Este mecanismo, provavelmente, foi responsável pela diminuição do comprimento de raízes (Figuras 1B, 1G e 1H), de aproximadamente 43,5; 32,2; 12,2 e 2,2%, na relação 100:0; 75:25; 50:50 e 0:100 (NH 4 + :NO 3 -), respectivamente, quando comparadas com os efeitos observados na relação 25:75.…”
Section: Figuraunclassified